2018
DOI: 10.21608/sjfop.2018.12818
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Multiplication of Vangueria Edulis as Affected by Cytokinins and Medium Type

Abstract: during the period from 2015 to 2017, to investigate the effect of cytokinin type and concentration (BAP, 2-iP and kin, at either 0.0, 1.0, 2.0 and 3.0 ppm) as well as medium type (MS or B5) on micro-shoots multiplication of in vitro cultured rare ornamental plant, Vangueria edulis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…BAP is directly linked to a high rate of shoot multiplication and has been found to be efficient in the multiplication of several species (Rodrigues et al, 2016;Emer et al, 2018;Enkhbileg et al, 2019). El-Bagoury et al (2018), andFreitas et al (2016), indicated the concentration of 1 ppm BAP as the best performance for multiplication of Vangueria edulis and Annona emarginata, respectively. At this dose there was the maximum abscission content, despite being half of the abscess found in ZEA, it is admitted that for baraúna, BAP doses below 0.8 are favorable to avoid abscission.…”
Section: Discussionmentioning
confidence: 99%
“…BAP is directly linked to a high rate of shoot multiplication and has been found to be efficient in the multiplication of several species (Rodrigues et al, 2016;Emer et al, 2018;Enkhbileg et al, 2019). El-Bagoury et al (2018), andFreitas et al (2016), indicated the concentration of 1 ppm BAP as the best performance for multiplication of Vangueria edulis and Annona emarginata, respectively. At this dose there was the maximum abscission content, despite being half of the abscess found in ZEA, it is admitted that for baraúna, BAP doses below 0.8 are favorable to avoid abscission.…”
Section: Discussionmentioning
confidence: 99%